Rational Design, Synthesis and Evaluation of Novel Second Mitochondrial-Derived Activators of Caspase (Smac) Mimetics That Induce Apoptosis in Human MDA-MB-231 Breast Cancer Cell Line - Cheema, Tasbir (Université d'Ottawa / University of Ottawa, 2012)
Programmed cell death (apoptosis) is the most common mechanism of cell death in eukaryotes. The ability of cancer cells to evade and inhibit apoptosis has become a hallmark feature of cancer. This is accomplished through a family of proteins known as the inhibitor of apoptosis proteins (IAPs). X-Linked inhibitor of apoptosis protein (XIAP) is one of the best characterized IAPs. XIAP suppresses apoptosis by forming complexes with cysteine-aspartic proteases (caspase), through one of its baculovirus IAP repeat (BIR) domains. Its activity is endogenously antagonized by a second mitochondria derived activator of caspase (Smac). The anti-apoptotic behaviour of XIAP and the critical role it plays in the apoptotic program makes the Smac-XIAP interaction an important drug target. To this end, our laboratory is interested in synthesizing biologically related Smac mimetics which can induce apoptosis in a MDA-MB-231 cell line. Efforts have focused on (1) understanding BIR domain binding sites which allow for this interaction, and (2) the design and synthesis of molecules which are much more effective at inducing apoptosis compared to other well known analogues. Through the synthesis and evaluation of various divalent Smac mimetics we have been able to support the hypothesis that the likely binding site on XIAP is the BIR3 domain. As well, through the synthesis of a library of novel compounds, as described in the thesis, we have been able to assess the nature of the linker which joins the two tetrapeptide units. In our effort to understand which domains Smac binds with, various divalent analogues were synthesized containing MeAVPI-linker-IPVMeA (forward-reverse) and MeAVPI-linker-MeAVPI (forward-forward) sequence, which incorporated linkers with varying degrees of flexibility. We hypothesized that the forward-forward divalent mimetics would have decreased activity compared to the peptides synthesized in a forward-reverse fashion. Lastly, information gathered from structure activity relationship (SAR) studies have shown that substituting the lysine (P2) and isoleucine residues (P4) in the AVPI protein can create more potent inducers of apoptosis than its native AVPI sequence. As one of the most potent Smac mimetic that has been previously made known contains an alkyne bridge at P2 and a large hydrophobic moiety at P4, we hypothesized that similar Smac mimetics containing a propargyl glycine residue at P2 and a bulky hydrophobic moiety at P4 will be much more potent in inducing apoptosis.
Keywords: Apoptosis; Smac; XIAP; X-Linked inhibitor of apoptosis protein; Caspase; Inhibitor of apoptosis proteins; BIR domain